Towards translating research to clinical practice: Novel Strategies for Discovery and Validation of Biomarkers for Brain Injury - Kevin K. W. Wang; Stefania Mondello; Ronald L. Hayes; Andras Buki; Frank C. Tortella (Frontiers Media SA, 2015)
Traumatic brain injury (TBI) is a major cause of death and disability and one of the greatest unmet needs in medicine and public health. TBI not only has devastating effects on patients and their relatives but results in huge direct and indirect costs to society. Although guidelines for the management of patients have been developed and more than 200 clinical trials have been conducted, they have resulted in few improvements in clinical outcomes and no effective therapies approved for TBI. It is now apparent that the heterogeneity of clinical TBI is underlain by molecular phenotypes more complex and interactive than initially conceived and current approaches to the characterization, management and outcome prediction of TBI are antiquated, unidimensional and inadequate to capture the interindividual pathophysiological heterogeneity. Recent advances in proteomics and biomarker development provide unparalleled opportunities for unraveling substantial injury-specific and patient-specific variability and refining disease characterization. The identification of novel, sensitive, objective tools, referred to as biomarkers, can revolutionize pathophysiological insights, enable targeted therapies and personalized approaches to clinical management. In this Research Topic, we present novel approaches that provide an infrastructure for discovery and validation of new biomarkers of acute brain injury. These techniques include refined mass spectrometry technology and high throughput immunoblot techniques. Output from these approaches can identify potential candidate biomarkers employing systems biology and data mining methods. In this Research Topic, we present novel approaches that provide an infrastructure for discovery and validation of new biomarkers of acute brain injury. These techniques include refined mass spectrometry technology and high throughput immunoblot techniques. Output from these approaches can identify potential candidate biomarkers employing systems biology and data mining methods. Finally, suggestions are provided for the way forward, with an emphasis on need for a multidimensional approach that integrate a panel of pathobiologically diverse biomarkers with clinical variables and imaging-based assessments to improve diagnosis and classification of TBI and to develop best clinical practice guidelines.
English
Keywords: Traumatic Brain Injury; Brain Injury; discovery; clinical practice; biomarker